การวิเคราะห์ความหลากหลายของยีนที่สร้างโปรตีนบนผิวเมอร์โรซอยต์ชนิดที่ 1 ของพลาสโมเดียม ฟัลซิปารั่ม ในมิติเวลาและสถานที่ของประเทศไทย - วฒิภรณ์ สายชนะพันธ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
It Malaria remains the main cause of death in many tropical countries including Thailand. Efforts on malaria control focusing on humans, vectors and parasites have been hindered by the widespread occurrence of anti-malarial drug resistant parasites and insecticide resistant vectors. Therefore, development of a malaria vaccine is mandatory. One of the promising vaccine candidates for asexual blood stage vaccine of Plasmodium falciparum is protein of ~200 kDa expressed on the merozoite surface, designated merozoite surface protein 1 (PfMSP1). Several lines of evidence have indicated that the N-terminal and C-terminal parts of this part contained epitopes targeted by host protective immune responses. Analysis of PfMSP1 among natural parasite populations reveals that the C-terminal part exhibits microheterogeneity of sequences whereas the N-terminal part is characterized by 3 major allelic types with MAD20, K1 and RO33 as representative prototypes. Both the K1 type and the MAD20 type possess tripeptide repeats with sequence and size polymorphism among isolates whereas RO33 type exhibits low sequence variation with no apparent repeats. Because immunity against block 2 of PfMSP1 is allele-specific, a rational vaccine design requires knowledge on allelic distribution of PfMSP1 block 2 among natural P. falciparum populations in terms of space and time. In this study, we have developed a simple polymerase chain reaction (PCR) method for strain differentiation of P. falciparum based on the polymorphic block 2 of PfMSP1. The method was sensitive to detect as few as 5 parasites in the samples whereas specific alleles of block 2 could be unequivocally determined. Minor parasite populations in isolates containing multiple clone infections were also detected by the method. To explore the allelic distribution of block 2 of PfMSP1, 349 P. falciparum isolates from Chantaburi (n=49), Yala (n=124) and Tak (n=177) provinces were included in this analysis. MAD20, K1 and RO33 allelic types were identified in 151, 65 and 189 isolates, respectively. Multiple clone infections were observed in 46 of these isolates. The distribution of these allelic types was variable among these endemic areas whereas seasonal difference was not remarkable. Direct sequencing of 60 of these isolates that had single allelic types based on PCR has identified 15 new MAD20 sequences, designated M13, M14, M30, M31, M32, M33, M37, M38, M39, M40, M44, M45, M49, M53 and M63 that contained 5 to 14 tripeptide repeat units. The M47 type predominated among MAD20 allelic types (16 sequences). Meanwhile, 4 new K1 sequence types from Chantaburi province (K2, K8, K11 and K13) containing 5 to 12 tripeptide repeat units were detected with K10 as a predominant sequence type. On the other hand, the sequence of RO33 type was identical among 23 isolates examined in this study whose sequence was novel. Therefore, the PCR method developed in this study should be applicable for large-scale population genetic analysis of P. falciparum population based on the PfMSP-1 locus whereas direct sequencing further provides detail epidemiological evidence on parasite clone. These findings are important for PfMSP1 block 2-derived vaccine.